KOMPOSISI DAN STRUKTUR HUTAN RIPARIAN SEBAGAI PENAHAN GELOMBANG DI DESA SEMAYANG KABUPATEN KUTAI KARTANEGARA - Daryadi A, Muhammad; Hendra, Medi; Hariani, Nova (Universitas Tanjungpura, 2019)
AbstractThis study aimed to determine the composition and structure of Semayang forest and the Importance Value Index (IVI) of riparian forest in its role of reducing the wave rate. The method used is multilevel plot method of 20x20 m for sampling of tree level, 5x5 m for sapling level and 2x2 m for seedling level. The result showed that the highest Importance Value Index at tree level was dominated by 3 species, they were L. javanicum (101,663), M. speciosa (76,201) and G. renghas (65,962). At sapling level dominated by P. indica (102,990). At seedling level dominated by M. pigra (95,004)andP. brevistipitata (70,109). In addition, Semayang riparian forest has an ecological function as a wave retaining. It can be seen based on the vegetation density and horizontal structure of species that make up the forest. Vegetation density is predicted to reduce the rate of Semayang lake waves that occur during flood season.Â Keywords: Composition and Structure, Riparian Forest, Semayang Lake.Â